The effects of muscle fatigue on shoulder proprioception and forehand stroke accuracy in Chinese elite table tennis athletes - Chen, Z.; Zhao, T.; Shen, Y.; Ren, S.; Sun, L. (BMC Sports Science, Medicine and Rehabilitation, 2025)
This study explores the relationship between shoulder proprioception and landing point accuracy in Chinese elite table tennis athletes, particularly under fatigue conditions. A total of 19 male athletes participated, with their shoulder proprioception tested using an ISOMED 2000 isokinetic muscle tester. The tester measured proprioception acuity in both pre-fatigue and post-fatigue conditions, alongside performance in a hitting task assessed with a high-speed serve machine. Results indicated a significant correlation between proprioception and stroke performance, especially in internal and external rotation directions (p < 0.01). After fatigue, proprioception in both the racket-holding and non-racket-holding hands significantly decreased in internal and external rotations (p < 0.01 for both hands), with no significant change in vertical extension (VE). Additionally, the performance of the hitting task after fatigue significantly declined in the racket-holding hand (p < 0.01). These findings suggest that shoulder proprioception plays a crucial role in stroke accuracy and fatigue recovery, providing valuable insights for training, rehabilitation, and performance optimization in table tennis.